RAF-Inhibitoren - Utikal, Jochen; Brummer, Tilman; Zenz, Thorsten (Der Onkologe, 2017)
Background: Inhibition of the Raf-mitogen-activated protein kinase (RAF-MAPK) pathway with BRAF (or MEK) inhibitors is highly effective as targeted therapy in tumors driven by BRAF mutations, such as melanomas; however, the development of resistance towards these inhibitors is a major problem. Objective: This article gives an overview of this signaling pathway, reports on the latest studies and side effects of this class of substances and discusses potential strategies to overcome emergence of resistance. Methods: This work is based on a review and an evaluation of the literature. Results: BRAF inhibitors have been approved for monotherapy of advanced BRAF mutation-driven malignant melanoma since 2011. This targeted therapy has demonstrated significant improvements in progression-free and overall survival. The successful use of BRAF inhibitors in melanoma was recently followed by their application in other malignant diseases featuring the BRAF-V600E mutation. BRAF inhibitors are generally well tolerated. However, different BRAF inhibitors exhibit different toxicity profiles. Conclusion: Combination therapies with MEK inhibitors can improve treatment response and overall survival.